Mind the Gap: Animal Protection Law and Opinion of Sheep Farmers and Lay Citizens Regarding Animal Maltreatment in Sheep Farming in Southern Brazil - Vanessa Souza Soriano; Clive Julian Christie Phillips; Cesar Augusto Taconeli; Alessandra Akemi Hashimoto Fragoso; Carla Forte Maiolino Molento (Animals, 2021)
We aimed to study the gaps between the law and sheep farmer and citizen opinions regarding animal maltreatment by discussing the risk of sheep maltreatment in regular farming practices in Southern Brazil. We surveyed the perception of 56 farmers and 209 citizens regarding general animal and specific on-farm sheep maltreatment issues. The main themes from these two groups about the key components of animal maltreatment were similar: failing to provide for the basic animal needs (27.0%; 96 of 355 total quotes) and aggression or physical abuse (23.9%; 85/355). However, citizens (19.8%; 60/303) were more sensitive than farmers (9.6%; 5/52) to animal stress, suffering, fear, pain or painful procedures (p < 0.05). The perspective of citizens was closer than that of farmers to expert definitions for three situations: emaciation, movement restriction and tail docking without anesthetic use (p < 0.05). More citizens (71.6%; 116/162) than sheep farmers (49.0%; 24/49) believed that animal maltreatment occurs in sheep farming (p < 0.05), but nearly half of the farmers recognized sheep maltreatment within regular production practices. Most citizens (86.4%; 140/162) and all farmers (100.0%; 0/51) were unaware of any Brazilian animal protection law. Most citizens (79%; 131/167) stated that they would not purchase products from animals exposed to maltreatment. We suggest painful procedures as a major risk of animal maltreatment in sheep farming and a priority issue. With the many decades of animal protection laws and scientific recognition of animal sentience and welfare requirements, the level of cognitive dissonance and practical contradictions observed in our results indicate that mitigation policies are urgently needed.